Självskadebeteende och riskbeteende för ätstörningar hos tonåringar: förekomst, samband och intervention med expressivt skrivande - Hellmo,Maria; Svensson,Magdalena (2007)
The purpose of the present essay, as part of the project Self esteem and Life circumstances among teenagers, was to investigate the rate of both deliberate self-harm (DSH) and risk behaviour related to eating disorders in 14-year-old swedish adolescents, gender differences in DSH, and possible correlations between DSH and risk behaviours related to eating disorder. In addition, the effects of expressive writing (Pennebaker & Beall, 1986) on DSH and risk behaviours related to eating disorders were investigated. Data from two pilot studies are included. In total, 198 14-year-olds from four different schools in southern Sweden participated. For the purpose of measuring the rate of DSH, a simplified version of Gratz's (2001) Deliberate Self-Harm Inventory (DSHI) was used. Results showed that 40.2 % of the adolescents reported having engaged in some kind of deliberate self-harm behaviour at least once during the last 6 months. 7.8 % reported having engaged in DSH behaviour ten times or more. There were no overall gender differences. However, the girls reported significantly higher rates on two items: biting oneself so that the skin is broken and preventing wounds from healing. In order to measure risk behaviour related to eating disorder, RiBED-8 (Risk Behaviours related to Eating Disorder), a screening instrument developed by Waaddegaard, Thoning and Petersson (2003) was used. Because the instrument is validated only for girls, only they were included in the analysis. Results showed that 22.2 % of girls are at risk of developing an eating disorder. High rates of DSH were significantly associated with high rates of risk behaviour related to eating disorder. Both studies included are explorative; the larger having a quasi-experimental design and the smaller an experimental design. Only the quasi-experimental design, contrary to expected, shows a significantly negative effect on DSH for participants in expressive writing. When analysed by gender, results are significant only for boys. Analyses of the experimental study revealed no indications of effect on DSH. Neither were any indications of effect on risk behaviours related to eating disorders found for girls.
Keywords: Psykiatri; psychosomatics; clinical psychology; Psychiatry; treatment; adolescents; expressive writing; eating disorder; parasuicide; self-mutilation; deliberate self-harm; behandling; prevention; tonåringar; expressivt skrivande; självskadebeteende; ätstörningar; klinisk psykologi; psykosomatik; Social sciences; Samhällsvetenskaper; Psychology; Psykologi; Applied and experimental psychology; Tillämpad och experimentell psykologi